Dual Antiplatelets Reduce Microembolic Signals in Patients with Transient Ischemic Attack and Minor Stroke: Subgroup Analysis of CLAIR Study. (October 2014) - Lau, Alexander Y.; Zhao, Yudong; Chen, Christopher; Leung, Thomas W.; Fu, Jianhui; Huang, Yining; Suwanwela, Nijasri C.; Han, Zhao; Tan, Kay Sin; Ratanakorn, Disya; Markus, Hugh S.; Wong, Ka Sing; et al.
Background: Short course of dual antiplatelet therapy for early secondary prevention is a promising treatment for patients with minor stroke or transient ischemic attack at high risk of recurrence. Methods: We examined the efficacy and safety of dual antiplatelets in patients with transient ischemic attack or minor stroke, defined as National Institute of Health Stroke Scale scores 0–3, in a subgroup analysis of Clopidogrel plus aspirin versus Aspirin alone for Reducing embolization in patients with acute symptomatic cerebral or carotid artery stenosis (CLAIR) study. Microembolic signals on transcranial Doppler monitoring was used as surrogate marker for recurrent stroke risk. Patients with ≥1 microembolic signals at baseline were randomized to receive dual therapy (aspirin 75–160 mg daily and clopidogrel 300 mg day 1 then 75 mg daily) or monotherapy (aspirin 75–160 mg daily) for seven-days. Results: Sixty-five of 100 patients recruited had transient ischemic attack or minor stroke: 30 received dual therapy and 35 received monotherapy. Mean onset-to-randomization was 2·3 days in dual therapy group and 3·2 days in monotherapy group ( P = 0·03). At day 7, the proportion of patients with ≥1 microembolic signals was 9 of 29 patients in dual therapy group and 18 of 34 patients in monotherapy group (adjusted relative risk reduction 41·4%, 95% CI 29·8–51·1, P < 0·001). The median number of microembolic signals on day 7 was 0 in dual therapy group and 1·0 in monotherapy group ( P = 0·046). No patients had intracranial or severe systemic hemorrhage. Conclusions: Early dual therapy with clopidogrel and aspirin reduces microembolic signals in patients with minor ischemic stroke or transient ischemic attack, without causing significant bleeding complications.